2000
DOI: 10.1093/carcin/21.9.1655
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention studies of the flavonoids quercetin and rutin in normal and azoxymethane-treated mouse colon

Abstract: In this study we investigated the chemopreventive effects of quercetin and rutin when added to standard AIN-76A diet and fed to normal and azoxymethane (AOM)-treated mice. Early changes in colonic mucosa were analyzed, including colonic cell proliferation, apoptotic cell death, cyclin D(1) expression and focal areas of dysplasia (FAD). The findings show that the number of colonic epithelial cells per crypt column increased (P: < 0.01) in each normal mouse group fed the flavonoids; AOM administration increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
74
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(81 citation statements)
references
References 50 publications
5
74
0
2
Order By: Relevance
“…The toxicity of quercetin at higher concentrations (50 M to 100 mM) toward cells in culture, in particular cancer cells, is well established and has been linked to an apoptotic mode of death (15,16,(21)(22)(23). However, little is known regarding the precise mechanism of quercetin-induced toxicity in other cell systems, and nothing is known of its effects on neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The toxicity of quercetin at higher concentrations (50 M to 100 mM) toward cells in culture, in particular cancer cells, is well established and has been linked to an apoptotic mode of death (15,16,(21)(22)(23). However, little is known regarding the precise mechanism of quercetin-induced toxicity in other cell systems, and nothing is known of its effects on neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent evidence has shown that quercetin is extensively metabolized to O-methylated and glucuronide metabolites during absorption in the small intestine and in the liver (17,18), and such metabolites should be taken into consideration to provide in vivo relevance for any mechanism. Quercetin itself has been thoroughly investigated for its abilities to express anti-proliferative effects (19,20) and induce death predominantly by an apoptotic mechanism in cancer cell lines (21)(22)(23). For example, it has been observed to induce caspase-3 activation in the malignant cell line HPB-ALL (24), activate caspase-3 and caspase-9, release cytochrome c in HL-60 cells (25), and induce chromatin and nuclear fragmentation in colonic cancer cells (20).…”
mentioning
confidence: 99%
“…Animal (Deschner et al, 1991;Yang et al, 2000) and in vitro studies suggest that quercetin exerts a preventive effect against cancer (Kawaii et al, 1999), but less is known about quercetin glucosides. Hollman et al (1995) show that 52% of the quercetin glucosides from onions was absorbed, whereas only 24% of free quercetin was absorbed in human model.…”
mentioning
confidence: 99%
“…As a class, fl avonoids are best known for their antioxidant activities (Bais et al 2003), but they also serve as communication signals between cell membranes, as regulators of cell growth, inducers of detoxifying enzymes, and inhibitors of seedling germination and growth (Macias et al 1997;Yang et al 2000;Hoagland & Williams 2004).…”
Section: Introductionmentioning
confidence: 99%